2012
DOI: 10.1007/s10468-012-9373-z
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of Nilpotent Leibniz Algebras

Abstract: Abstract. W. A. Moens proved that a Lie algebra is nilpotent if and only if it admits an invertible Leibniz-derivation. In this paper we show that with the definition of Leibniz-derivation from [17] the similar result for non Lie Leibniz algebras is not true. Namely, we give an example of non nilpotent Leibniz algebra which admits an invertible Leibniz-derivation. In order to extend the results of paper [17] for Leibniz algebras we introduce a definition of Leibniz-derivation of Leibniz algebras which agrees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
0
26
0
2
Order By: Relevance
“…In [10] it was proved that a finite-dimensional Leibniz algebra over a field of characteristic zero which admitting an invertible derivation is nilpotent. The Lemma is proved.…”
Section: 5mentioning
confidence: 99%
“…In [10] it was proved that a finite-dimensional Leibniz algebra over a field of characteristic zero which admitting an invertible derivation is nilpotent. The Lemma is proved.…”
Section: 5mentioning
confidence: 99%
“…In paper [34] a generalization of derivations and pre-derivations of Lie algebras is defined as a Leibnizderivation of order k. Moens proved that a finite-dimensional Lie algebra over a field of characteristic zero is nilpotent if and only if it admits an invertible Leibniz-derivation. After that, Fialowski, Khudoyberdiyev and Omirov [13] showed that with the definition of Leibniz-derivations from [34] the similar result for non-Lie Leibniz algebras is not true. Namely, they gave an example of non-nilpotent Leibniz algebra which admits an invertible Leibniz-derivation.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the structure theory and other properties of Leibniz algebras was initiated by Loday in [23]. Leibniz algebras were also studied in [12,15,20,28]. Zinbiel algebras were introduced by Loday in [22].…”
Section: Introductionmentioning
confidence: 99%